The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2174/156652409789105561
|View full text |Cite
|
Sign up to set email alerts
|

HSP27: Mechanisms of Cellular Protection Against Neuronal Injury

Abstract: The heat shock protein (HSP) family has long been associated with a generalized cellular stress response, particularly in terms of recognizing and chaperoning misfolded proteins. While HSPs in general appear to be protective, HSP27 has recently emerged as a particularly potent neuroprotectant in a number of diverse neurological disorders, ranging from ALS to stroke. Although its robust protective effect on a number of insults has been recognized, the mechanisms and regulation of HSP27's protective actions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
106
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 118 publications
(155 reference statements)
0
106
0
3
Order By: Relevance
“…As a high-molecular-mass homo-oligomer, mammalian HSP27 is known to direct the refolding of denatured proteins (31). Our data suggest that the Rit-p38-MK2 signaling axis functions as a regulator of HSP27 phosphorylation, with phosphorylation reported to result in HSP27 oligomer dissociation, release of scaffolded AKT, and a loss of chaperone activity (31).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As a high-molecular-mass homo-oligomer, mammalian HSP27 is known to direct the refolding of denatured proteins (31). Our data suggest that the Rit-p38-MK2 signaling axis functions as a regulator of HSP27 phosphorylation, with phosphorylation reported to result in HSP27 oligomer dissociation, release of scaffolded AKT, and a loss of chaperone activity (31).…”
Section: Discussionmentioning
confidence: 82%
“…The stress-responsive protein HSP27 (heat shock protein 27) is rapidly phosphorylated in cells responding to both extracellular stimuli and a variety of stresses (14) and has been implicated in stress-dependent AKT activation (31). HSP27 normally exists as a high-order oligomer and has been shown to contribute to the regulation of cytoskeleton dynamics (26) and protein refolding (12), and overexpression of HSP27 has a potent antiapoptotic effect against a variety of cellular stresses (3).…”
mentioning
confidence: 99%
“…Thus, Hsp27 may exert a proinflammatory effect, both through inducing a proinflammatory reaction (e.g., IL-8) and reducing the production of the anti-inflammatory factors (e.g., CD40 ligand and TGF-␤ 1 ) (Liu et al, 2010). In addition, Hsp27 may also function as an indirect anti-apoptotic molecule (Concannon et al, 2003) by inhibiting the proapoptotic proteins caspase-3 (Stetler et al, 2009) and Bax (Havasi et al, 2008). Since both TGF-␤ 1 and CD40 ligand may be involved in apoptosis during inflammation (Calingasan et al, 2002;Schuster and Krieglstein, 2002), reduced TGF␤1 and CD40 ligand levels induced by Hsp27 may add to the anti-apoptotic effect of Hsp27.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, special attention has been paid to a 27 kDa heat shock protein (HSP27) that is constitutively expressed in some populations of neurons. HSP27 plays an important role in cellular defense mechanisms[242526]. A previous study showed that, 1 week after avulsion of the spinal nerve root, small motor neurons (< 500 Âľm 2 ) negative for HSP27 immunoreactivity died and only large (> 500 Âľm 2 ) HSP27-positive motor neurons survived in the spinal cord ventral horn[3].…”
Section: Introductionmentioning
confidence: 99%